Desain model penguasaan konten melalui teknik modelling simbolik untuk mengembangkan karakter Mahasiswa - Siti Fitriana; Gregorius Rohastono Ajie; Suhendri Suhendri (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2016)
The purpose of the research is the development of student character and know the effectiveness of the content mastery service with the technique of modeling. The experimental method. The population of the research is the students of BK semester V amounted to 212 students. The pre-test recapitulation obtained a total score of 2205 with an average of 105. The total score is classified into low character category with the percentage of 14.3%. From the empirical data above, the researcher wants to make the low student character become moderate, which is being able to increase to high and high become very high. So the steps taken is to provide mastery of the content through modeling techniques to develop student character BK. Post-test results after given content mastery service to develop the character, obtained data that 76% of students are in very high category and 24% high. While the scores obtained medium and low characters are absent or 0%. The content mastery service model with developed modeling techniques can be effective by providing examples and models for students who are intensive and ongoing.